PEMAHAMAN MODERASI ISLAM SANTRIWATI MELALUI PENGAJARAN KITAB KUNING DI PESANTREN MAMBAUS SHOLIHIN - Novia Andriani; Himmah Al Ulya; Haniatul Khoiroh; Muhammad Makinuddin (Makkah: Journal Of Islamic Studies, 2025)
Islamic moderation is an important focus in Islamic boarding school education to shape tolerant, balanced, and just students. The yellow book, as a classic source of religious education, is believed to contain values ​​of moderation that can be internalized through daily learning and practice. This study aims to explore how female students understand and apply the values ​​of Islamic moderation through the teaching of the yellow book at the Mambaus Sholihin Islamic Boarding School. The study used a qualitative approach with a descriptive phenomenological design. Data were collected through participant observation, semi-structured in-depth interviews with 17 informants (female students, female teachers, and caregivers/curricula), and documentation of the yellow book material and Islamic boarding school activities. Data analysis was conducted thematically to identify patterns of understanding and internalization of the values ​​of moderation. The results of the study indicate that female students understand moderation through learning etiquette, tolerance of differences in schools of thought, patience in learning, and experiences of living together with students from across regions. Ustadzah emphasizes moderation through learning methods that foster politeness, varied explanations of Islamic jurisprudence, and a balance between worship and social morals. Caregivers and the curriculum ensure that moderation is the direction of Islamic boarding school education and the basis for designing the yellow book material. Overall, the value of Islamic moderation is internalized through a combination of materials, methods, teacher role models, and Islamic boarding school culture. These findings confirm that teaching the yellow book in Islamic boarding schools not only transfers religious knowledge but also shapes the moderate character of female students. The integration of materials, methods, and role models creates an educational ecosystem that consistently supports tasamuh (compassion), tawasuth (religious tolerance), i'tidal (independent tolerance), and tawazun (independent tolerance). Yellow book-based education in Islamic boarding schools has proven effective as a means of internalizing the values ​​of Islamic moderation, providing a model for other Islamic educational institutions in developing tolerant and civilized students.